Antimicrobial resistance genes present in the faecal microbiota of free‐living Galapagos tortoises (Chelonoidis porteri). (24th August 2019) - Nieto‐Claudin, Ainoa; Esperón, Fernando; Blake, Stephen; Deem, Sharon L.
Abstract: Antimicrobial resistance (AMR), encoded by plasmid‐mediated AMR genes (ARGs), is an increasing global public health threat. Wildlife play a fundamental role as sentinels, reservoirs and potential vectors of ARGs. For the first time in Galapagos, we have identified and quantified the presence of ARGs in free‐living giant tortoises ( Chelonoidis porteri ). We performed ARG analyses by quantitative PCR of faeces collected from the cloaca of 30 tortoises widely distributed across Santa Cruz Island. Validated samples ( n = 28) were analysed by a panel of up to 21 different ARGs and all 28 tortoise samples were positive to one or more genes encoding resistance. Thirteen of 21 tested ARGs were present in at least one sample, and 10 tortoises (35.7%) had a multi‐resistant pattern. We recommend additional research so we may more fully understand resistance patterns across taxa and geographical locations throughout the Galapagos archipelago, and the implications of ARGs for the health of wildlife, domestic animals, and humans. In this study, we found 100% of sampled giant tortoises had ARGs present in their faeces, suggesting a large‐scale distribution of these genes within the archipelago.